Empire of Words : The Reign of the OED - Willinsky, John, 1950- (Book collections on Project MUSE., 2001)
What is the meaning of a word? Most readers turn to the dictionary for authoritative meanings and correct usage. But what is the source of authority in dictionaries? Some dictionaries employ panels of experts to fix meaning and prescribe usage, others rely on derivation through etymology. But perhaps no other dictionary has done more to standardize the English language than the formidable twenty-volume Oxford English Dictionary in its 1989 second edition. Yet this most Victorian of modern dictionaries derives its meaning by citing the earliest known usage of words and by demonstrating shades o.